Wronskians and subspaces of certain fourth order differential equations - G. J. Etgen; Willie E. Taylor (International Journal of Mathematics and Mathematical Sciences, 1980)
The objectives of the paper are to study the behavior of Wronskians of solutions of the fourth order differential equations and to relate this behavior with the oscillations of these equations, as well as to the structure of the subspaces of the solution spaces of the equations.